ChemInform Abstract: Aromaticity from the Viewpoint of Molecular Geometry: Application to Planar Systems. Issue 32 (24th July 2014) - Krygowski, Tadeusz M.; Szatylowicz, Halina; Stasyuk, Olga A.; Dominikowska, Justyna; Palusiak, Marcin
Abstract Review: 433 refs.